2006
DOI: 10.1016/j.jcat.2006.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically active states of Ru(0001) catalyst in CO oxidation reaction

Abstract: Identifying the composition of the catalytically active state of metal catalysts under dynamic operating conditions is of particular importance for oxidation catalysis. We report here new insights into the chemical identity of different catalytically active states formed on a Ru(0001) catalyst during the CO oxidation at different reaction temperatures. The changes in the surface composition of the Ru catalyst and the CO 2 yield under varying reaction conditions in the 10 -4 to 10 -1 mbar pressure range were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 30 publications
7
97
0
4
Order By: Relevance
“…Two additional components at 286.0 and 288.2 ± 0.2 eV are assigned to oxygen bound carbon species; alcohol/carbonyl groups and formate groups respectively [23], [24] and [25]. The Ru 3d 5/2 peak at 280.0 eV is very close to the binding energy previously measured on clean metallic Ru (0 0 0 1) in the same set-up [26]. The Co 2p 3/2 peak (solid black line) shown in Fig.…”
Section: Comparison Of Srm and Wgs Reactions Over Ptruco Catalystsupporting
confidence: 80%
“…Two additional components at 286.0 and 288.2 ± 0.2 eV are assigned to oxygen bound carbon species; alcohol/carbonyl groups and formate groups respectively [23], [24] and [25]. The Ru 3d 5/2 peak at 280.0 eV is very close to the binding energy previously measured on clean metallic Ru (0 0 0 1) in the same set-up [26]. The Co 2p 3/2 peak (solid black line) shown in Fig.…”
Section: Comparison Of Srm and Wgs Reactions Over Ptruco Catalystsupporting
confidence: 80%
“…Ruthenium shows interesting catalytic properties for a number of industrially relevant applications including CO oxidation 1 and ammonia synthesis. 2,3 In particular, the latter has attracted much attention due to ruthenium's activity at significantly lower temperatures than traditional Haber−Bosch synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The O-TM-O trilayer structure has been shown to be an important surface oxide phase upon oxidation of TM surfaces. [25][26][27][28] The structural transformation between these surface oxide phases may exhibit a strong influence on oxide catalysis, which is worth exploring in detail. Using the FeO x -Pt inverse catalytic system, we have shown that metastable FeO bilayer nanostructures can be stabilized on Pt surfaces via the confinement effect exerted by the noble metal surfaces.…”
Section: Introductionmentioning
confidence: 99%